(untitled) (Annals of Medical Research, 2021)
Aim: The gold standard treatment of end-stage renal failure is kidney transplantation. In western countries, more than 80% of kidney transplants are cadaveric transplants, in Turkey, this ratio is below 25% due to insufficient cadaveric organ supply. In this study, we aimed to give a general assessment of cadaveric kidney transplant of patients on the waiting list of Istanbul University Medical Faculty General Surgery Organ Transplantation Unit.Material and Methods: Patients waiting for transplantation for a cadaveric kidney on National Organ Waiting List have been evaluated for demographic data, mean duration of dialysis, concomitant diseases, dialysis type, blood groups, end-stage renal failure etiologies, additional diseases that developed during kidney transplant waiting period, and their final status.Results: Two hundred and forty-four patients were included in the study. There were 122 female and 122 male. The median age was 52 (2-77) years. The most common etiology of renal failure was hypertensive nephrosclerosis. The median waiting time was 89 months (13-390). Though there was no difference between female and male patients according to median age, height and BMI, there was a significant difference according to waiting duration (F/M 113/75 months, p 0,017). In the last 1 year, 13 patients died while they were waiting for a kidney transplant and 17 patients lost their chance of kidney transplant due to developing diseases.Conclusion: To increase Turkey’s organ transplantation and cadaveric transplant donation on the waiting list we need to develop donation policy for a shorter period of dialysis and to ensure that patients receive transplantation earlier.Keywords: Dialysis period; kidney transplantation; cadaveric waiting list.